KOMUNIKASI ANTARMUKA PROGRAMABLE LOGIC CONTROLLER PADA MODBUS RTU SENSOR SUHU DAN KELEMBABAN UDARA DENGAN DATALOGGER - syaiful rachman; Zaiyan Ahyadi; Syarifudin Syarifudin (Universitas Nusa Cendana, 2022)
In this research, PLC (Programmable Logic Controller) was used as a component of Master and Slave components. Communication between Master and Slave used RS485 serial communication, and the basic functions of the Modbus protocol were the XY-MD02 SHT20 type temperature and humidity sensor which will be stored in the data logger to store temperature and humidity data from the implementation results in the PLC (Programmable Logic Controller) datalogger object software to obtain temperature and humidity data according to the address given by testing data sampling for 1 minute the results obtained by the communication system can work well, based on analysis using Modbus poll simulation results obtained with Function code, the type of command in the READ condition was obtained 04 ( 04 hex), then the result of address and quantity was 2 then the result of slave id with the address was 1.